THE EFFECT OF RISK, PROFITABILITY AND LIQUIDITY ON CAPITAL ADEQUACY - Fransisca Carindri; Untara Untara (Universitas Gunadarma, 2019)
The purpose of this research was to determine the effect of partial Non Performing Loan (NPL), Risk Index (ZRISK), Return on Assets (ROA), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Loan to asset Ratio (LAR) to the Capital Adequacy Ratio (CAR) on banking companies listed on the Stock Exchange. The research population was banking companies listed in Indonesia Stock Exchange during the three (3) year period from 2010 to 2012. The sample used in this research was determined using purposive sampling technique in which there are 29 companies that meet the criteria for sample selection. The analysis technique used is multiple linear regression and the processing of the data using SPSS v15.0. The results showed that the ROA, LDR, and LAR have no significant effect on CAR. While the NPL, Risk Index and NIM have significant effect on CAR. Predictive ability of the six independent variables on CAR was at 32.9 % while the remaining 77.1 % is influenced by other factors not included in the regression model.